Study on Automatic Recognition of Fabric Color and Matching to Standard Color Chip by Computer Vision and Image Analysis Technology (Journal of Fiber Bioengineering and Informatics, 2016)
The Artificial visual approach to detect fabric color is easy to be affected by light and experience. Inorder to overcome the shortcomings of errors, this paper presents a new method for matching betweentextile fabric color and standard color card automatically, and establishes the automatic matching systemfor 1925 kinds of Pantone TCX color swatches by using computer vision and image analysis. First,the scan images of Pantone TCX color were acquired, then we extracted effective color characteristicinformation from the images, and constructed the database of color features. Furthermore, we designedcolor layered model and matching model which based on ‘one to one’ Support Vector Machine (SVM).Through parameter optimization and identify training for SVM model, the accuracy of color identifying is96.89%. Finally, we used 296 unknown color samples for verification, the accuracy is 98.85%. The resultsshow that the research provides an effective auxiliary tool objectively and quickly for color measurement.